Compliance with Medication and Family Support for Hypertension Patients in the Work Area of the Talaga Biru Health Center Gorontalo City - Pangalo, Paulus; Buheli, Kartin L.; Bakari, Novalina (Poltekkes Kemenkes Gorontalo, 2021)
Hypertension was one problem in health sector because of its high incidence rate worldwide, and until now still increasing. According to WHO data in 2015, around 1.13 billion people in the worldwide suffer hypertension. It was estimated that 1.56 billion adults in the world will hypertension by 2025. Based on national research data in 2018, Gorontalo Province was 20th position with the number of cases of hypertension. Adherence to taking medication was one of the problems in the treatment of this disease. However, this adherence could overcome through monitoring by members of family regarding treatment, and determining whether to use health services or not. This study aims to determine the relationship between role of family with compliance treatment of patients in the working area of community health centers of Telaga Biru, Gorontalo city. This study used cross sectional research design with purposive sampling technique. Total of 34 respondents with hypertension obtained then dianalysis using Chi Square test. The results of show that the calculated X2 value of 18.2 and greater than the X2 table with p value = 0.000 (p<0.05). These findings indicate that role of the family was very influential on the regularity level of treating hypertension patients in the working area of the Telaga Biru Health Center, Gorontalo city. We conclude that regular treatment could improved through the role and duties of the family in controlling patients with hypertension